Proposal: Fundamental study of spectral slicing wavelength division multiplexing (WDM) system - Nasim, Ahmed; Syed Alwee Aljunid, Syed Junid, Prof. Dr.; R. Badlishah, Ahmad, Prof. Madya Dr.; Muthana, Yassen .K (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Arau, Perlis, Malaysia.